Analysis of Junior High School Students' Understanding in Determining the Sequence of Integers - Damayanti, Alifia; Sujiwo, Dimas Andhita Cahyo; Murtinasari, Frida (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study intends to analyze students' ability to determine the order of positive and negative integers and to identify the difficulties they experience in understanding the concept. The subject matter is important because many students still experience confusion in comparing and ordering integers, especially when negative numbers are involved. This type of research uses a qualitative-descriptive approach. This study was conducted in grade VI of a public junior high school 13, Jember, with 32 students selected based on the willingness of the school and teachers, but only 6 students who met the criteria were selected. The instruments used included a written test and in-depth interviews. The results showed that students' understanding of the ordering of positive and negative integers is relatively low. Students often face challenges in distinguishing and ordering positive and negative numbers, especially when dealing with number lines or mixed operations. The main factor contributing to students' challenges is a lack of understanding of the basic concepts of integers and their application on the number line. Students sometimes experience confusion regarding the order of numbers due to their incomplete understanding of numerical positions on the number line, as well as the principle of absolute value and the meaning of positive and negative signs. The results of this study are expected to provide a general overview of students' level of understanding and provide recommendations for effective learning strategies to improve their ability to correctly order integers.